From Paper to Pixels: The Transformation of Marketing into the Digital Omnichannel Era and Its Impact on Social Life (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2025)
The transformation away from traditional, fragmented marketing channels and toward a completely integrated omnichannel ecosystem has altered how brands interact with consumers. This MS will study the overall impact of digital omnichannel marketing on consumer social behavior, focusing on trust, privacy perspectives, social behavior behavior (Mawlud, 2025; Belk, 2013). Combining previous literature and using a simulated research framework, the current research investigates on how pervasive marketing in daily digital life creates (or affects) both social and economic outcomes (Lemon and Verhoef, 2016; Rahman, 2025); the impact on sales, customer lifetime value, return on investment (ROI), Customer Engagement Scores (CES) and efficiency of the customer experience (CX). Employing a mixed-methods approach, exploring quantitative measures of adoption and performance, and qualitative analysis of wider social impacts, the findings offer a comprehensive view of the omnichannel imperative. The findings and recommendations we generate may guide marketers, policy makers, and businesses to formulate ethical, culturally appropriate, and effective digital strategies to maximize business performance while protecting consumer well-being (Sassi, 2024; Davis, 1989).